Pharmacological treatment options for obesity in children with insulin resistance: a targeted review - Drozdowska, Marta; Borychowska, Emilia; Bystros, Aleksandra; Czudowska, Michalina; Gwóźdź, Karolina; Kurzątkowska, Klaudia; Marszałek, Dominika; Mierzejewska, Zofia; Ocimek, Aleksandra; Zawadzka, Magdalena (Quality in Sport, 2026)
Background. Childhood and adolescent obesity is an increasing global health concern. Many obese children develop insulin resistance, which contributes to metabolic complications including type 2 diabetes, dyslipidemia, hypertension, and non-alcoholic fatty liver disease. Although lifestyle modification remains the primary treatment, it is often insufficient in cases of severe obesity or marked insulin resistance. In recent years, pharmacological therapies have been increasingly used in pediatric obesity, but their efficacy and safety in insulin-resistant children are not fully established. Aim. This review aims to summarize current evidence on pharmacological treatment options for obese children with insulin resistance, with a focus on efficacy, safety, and research gaps relevant to clinical practice. Material and methods. A literature review was conducted using PubMed, MEDLINE, Scopus, and Web of Science. Studies evaluating pharmacological therapies such as metformin, GLP-1 receptor agonists, and orlistat were included. Randomized controlled trials, systematic reviews, meta-analyses, and observational studies reporting changes in BMI, metabolic parameters, and adverse events were analyzed. Conclusions. Available evidence suggests that pharmacological agents, including metformin, orlistat, GLP-1 receptor agonists, and phentermine/topiramate, can reduce body weight and improve metabolic outcomes in obese children and adolescents with insulin resistance. GLP-1 receptor agonists show the greatest BMI reduction. Safety profiles vary, with gastrointestinal adverse effects being most common. Long-term safety data, particularly in children under 12 years of age, remain limited, highlighting the need for individualized therapy and further research.